Special Issue on Multiphase Flows in Microfluidics: Fundamentals and Applications - Jianzhong Lin (Applied Sciences, 2023)
Microfluidics, a cutting-edge field involving various applications in advanced materials, new energy, single-cell/single-molecule studies, human health, biomedicine, and so forth, has advanced rapidly in the last two decades [...]